Prevalence of Depressive Symptoms among Young Adults in Szczecin - Marta Stępień-Słodkowska; Hanna Kostkiewicz; Katarzyna Kotarska; Bożena Kawicka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
Depressive disorders have become one of the greatest health problems of the modern society, with about 350 million people suffering from depression around the world (WHO). The aim of this study was to determine the prevalence of symptoms of depressed mood and symptoms indicating the possibility of depression or its progression among young people living in the city of Szczecin, Poland. Data from 150 students (107 women and 43 men) from one of the local universities constituted the material for this anonymous study which was based on the Beck Depression Inventory - 21 questions assessing the severity of depressive symptoms. Our results showed that 78% of women and 89% of men did not show symptoms of depression (Fig. 1). The incidence of mild depressive episodes was revealed in 15% of women and 7% of men, moderate episodes in 3% of women and 2% of men, and severe depression in 4% of women and 2% of men.